Antibacterial activity test of sweet arum mango peel extract gel preparation (Mangifera indica L.) against growth methicillin resistant staphylococcus aureus - Wulandari Wulandari; Evira Refryliana (Journal of Health Management and Pharmacy Exploration, 2023)
Inappropriate use of antibiotics can make bacteria’s reistance that cause skin diseases, the example is acne. Acne tretment usually uses synthethic drugs that causes side effects, so the alternative are used by plants that come from nature. On of the plats that has the potential as an antibacterial is the arum manis mango (Mangifera indica L.) because contains compounds that can inhibit the growth of Mathicillin Resistant Staphylococcus aureus. The research of this study was to determine the antibacterial activity of extract  gel’s arum manis mango peel to c. Extract of arum manis mango peel was obtained remaserated using 70% ethanol solvent. The extract obtined were phytochemicel screening and affirmation tests using the TLC (Thin Layer Chromatography) method to ensure the compounds contained. Arum manis mango peel is preparation of gel with a concentration of 5%, 10%, 15%, 20%, 25%. The results showed that extract of arum manis mango peel preparation gel with concentrations of 5%, 10%, 15%, 20%, 25%. The results showed that extract of arum manis peel preparation gel with concentration 5%, 10%, 15%, 20%, 25% showed significant difference in potential of antibacterial.